Evaluation of Islamic Education in a Pedagogic Perspective (Examining the Purpose and Meaning Behind the Islamic Values-Based Assessment Process) - Haikal, Muhammad Fajrin; Setiawan, Achmad Ghiyats; Supriadi, Udin; Budiyanti, Nurti (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
In this context, this article will discuss in depth the three problem formulations that have been identified including the purpose and meaning, the essential material that is evaluated, and the variety and steps of evaluation in conventional education and Islamic education. The research method used in this study is a qualitative approach with a library research method. This approach aims to understand the phenomenon in depth through analysis of various literature, such as books, scientific journals, articles, and other relevant documents. The results/findings obtained by the researcher at least bring up several subchapters of discussion including consisting of a Study of the Purpose and Meaning of the Evaluation of Conventional Education and Islamic Education, a Study of the Essential Material in the Evaluation of Conventional Education and Islamic Education, and a Study of the Variety and Steps of Evaluation of Conventional Education and Islamic Education. These findings highlight the importance of integrating Islamic values in the education evaluation system to produce individuals who are intellectually intelligent and have noble character. With holistic evaluation, future generations are expected to become individuals of faith, knowledge, and noble character.   Keywords: Pedagogics, Educational Evaluation, Islamic Values